Engineering Perspectives on Drying Technologies of Medicinal Plants: A Review on Kinetic Modelling and Bioactive Compounds Retention - Suresh, Kirthika; Kumaraswamy, Monisha; Sundaravadanam, Haridharshini; Kadirvel, Vijayasri; Thirumavalavan, Vennilavan; Ganesan, Nandhini Devi (Applied Science and Engineering Progress, 2026)
Medicinal plants, an integral part of the Indian traditional medicinal practices, are a reservoir of bioactive molecules proven to have therapeutic effects against various ailments. The post-harvest losses of medicinal plants have been estimated to range between 10-40% in Asian countries, including India, mainly due to improper handling, storage and packaging. Drying is an important post-harvest operation of plant materials that can significantly impact the functional bioactive compounds. This review aims to shed light on the various drying methodologies of medicinal plants, weighing their merits and limitations, and highlighting the latest advancements and current research. The review summarizes the influence of drying parameters on the stability and retention of bioactive compounds in medicinal plants, as well as focuses on the drying kinetic models employed to comprehend their moisture transport mechanism. In conclusion, the authors intend to address the major challenges and research gaps to offer insights for advancing research in improving the herbal drug quality through optimized drying conditions.